2005
DOI: 10.1002/ijc.21230
|View full text |Cite
|
Sign up to set email alerts
|

B7‐1 and B7‐2 act differentially in the induction of a T cell response: Their impact for a HLA‐matched and HLA‐mismatched anti‐tumor immunotherapy

Abstract: The efficacy of T cell-based immunotherapy is primarily due to efficient cellular activation that requires the engagement of 2 separate signals, i.e., via the T cell receptor complex and via costimulatory molecules the prototype of which is CD28. In cellular activation, the CD28 ligands B7-1 (CD80) and B7-2 (CD86) are thought to play nearly identical roles in T cell activation. We monitored the T cell response upon co-culture with HLA Class I-matched and mismatched renal carcinoma cells, respectively, that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…T cells were coincubated with paraformaldehyde-fixed wild-type (wt) MZ1257RC cells, B7-1-and B7-2-modified MZ1257RC cells, or MZ1257RC cells transfected with "empty" vector DNA. Cells of the B7-transduced MZ1257RC clones express about 1.25 ϫ 10 6 B7-1 and B7-2 molecules/cell, respectively (22). Upon coincubation with either B7-1 ϩ or B7-2 ϩ MZ1257RC cells T cells increased proliferation and cytokine secretion (interferon-␥, granulocyte macrophage colony-stimulating factor, tumor necrosis factor-␣, and IL-10), whereas coincubation with wt and mocktransfected MZ1257RC cells did not (data not shown).…”
Section: T Cells Express An Altered Pattern Of Proteins Upon B7mentioning
confidence: 99%
See 1 more Smart Citation
“…T cells were coincubated with paraformaldehyde-fixed wild-type (wt) MZ1257RC cells, B7-1-and B7-2-modified MZ1257RC cells, or MZ1257RC cells transfected with "empty" vector DNA. Cells of the B7-transduced MZ1257RC clones express about 1.25 ϫ 10 6 B7-1 and B7-2 molecules/cell, respectively (22). Upon coincubation with either B7-1 ϩ or B7-2 ϩ MZ1257RC cells T cells increased proliferation and cytokine secretion (interferon-␥, granulocyte macrophage colony-stimulating factor, tumor necrosis factor-␣, and IL-10), whereas coincubation with wt and mocktransfected MZ1257RC cells did not (data not shown).…”
Section: T Cells Express An Altered Pattern Of Proteins Upon B7mentioning
confidence: 99%
“…MZ1257RC cells were equipped with B7-1 and B7-2, respectively, by DNA transfection as described previously (12,22). MZ1257RC cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% (v/v) FCS, 2 mM L-glutamine, 10 IU/ml penicillin, 100 g/ml streptomycin, 10 mM sodium pyruvate, 100 mM Hepes, and 1ϫ non-essential amino acids.…”
Section: Isolation and Stimulation Of T Cells-peripheral Blood Mononumentioning
confidence: 99%
“…On the other hand, upon subcutaneous administration without adjuvant, ZPS activates the APCs differentially than during intra-abdominal challenge, or activate a different subset of APCs than those involved in ZPS presentation in the peritoneal cavity, resulting in the activation of regulatory T cells. We and others previously reported that ZPS can induce the upregulation of CD86 on APCs [28, 41] in vitro and signaling through CD86 is reported in promoting the generation of IL-10-producing T cells [77, 78]. Thus, it will be interesting to know if the differences that occur in the immune responses when ZPS is administered by intraperitoneal or subcutaneous routes are due to differences in the presentation of ZPS antigens by the APCs at these sites.…”
Section: Zps Modulates Cytokines Of the Immune Systemmentioning
confidence: 99%
“…These tumors have been shown to express T cell inhibitory molecules such as B7-H1 and ICOSL to engage their inhibitory counterparts on the T cell surface (Figure 2(a)). On the contrary, tumors that are induced to express costimulatory molecules that activate T cells, such as B7.1 (also known as CD80), and B7.2 (also known as CD86) are cleared by the immune system and thus may be used as a strategy to promote tumor immunity [148, 149]. …”
Section: Costimulation and Modulatory Molecules At The Immunologicmentioning
confidence: 99%